1996
DOI: 10.2105/ajph.86.8_pt_1.1155
|View full text |Cite
|
Sign up to set email alerts
|

A meningococcal vaccination campaign on a university campus: vaccination rates and factors in nonparticipation.

Abstract: OBJECTIVES. This study was undertaken to determine an accurate vaccination rate and identify factors influencing nonvaccination in a meningococcal vaccination campaign on a Connecticut university campus in May 1993. METHODS. Vaccination and student data were merged to determine demographic factors associated with nonvaccination. A case-control study examined reasons for nonvaccination. RESULTS. The estimated vaccination rate for students returning to the campus was 93%. Lower rates occurred among older student… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…This study found that vaccination rates decreased with increasing age and has provided a unique insight into vaccination amongst 20–25 year-olds, with data on uptake in this age-group not collected by PHE [ 35 ]. This finding concurs with other studies of student meningococcal vaccination and is highly relevant given that many students enter university at an older age, with 50.4% of the sample aged 20–25 years [ 6 , 8 , 9 ]. As this association was amplified upon multivariable analysis, it is unlikely to be attributable to demographics or health beliefs.…”
Section: Discussionsupporting
confidence: 91%
“…This study found that vaccination rates decreased with increasing age and has provided a unique insight into vaccination amongst 20–25 year-olds, with data on uptake in this age-group not collected by PHE [ 35 ]. This finding concurs with other studies of student meningococcal vaccination and is highly relevant given that many students enter university at an older age, with 50.4% of the sample aged 20–25 years [ 6 , 8 , 9 ]. As this association was amplified upon multivariable analysis, it is unlikely to be attributable to demographics or health beliefs.…”
Section: Discussionsupporting
confidence: 91%
“…Several researchers 10,11 have looked at factors predicting vaccination during mass meningococcal vaccination programs in response to cases of meningococcal disease. Gender, on-campus residence, and age have been shown to predict vaccination.…”
Section: Predictors Of Meningococcal Vaccinationmentioning
confidence: 99%
“…Gender, on-campus residence, and age have been shown to predict vaccination. [10][11] Ethnicity has also been shown to influence vaccination rates; we did not examine ethnicity in this study. 10 Our study has potential limitations.…”
Section: Predictors Of Meningococcal Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Serogroup C meningococcal disease (SCMD) outbreaks are an emerging health problem [1,2]. Outbreaks have been described in different settings, including universities, schools, correctional facilities, nightclubs, bars and a discotheque [3][4][5][6][7][8][9][10]. Factors which have been associated with serogroup C meningococcal infection are close contact with a case, preceding viral-like respiratory infections, crowded housing, alcohol consumption and active or passive smoking [4,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%